Emblems of passage art of Africa, Oceania, and the Americas: selections from Friends of Ethnic Art members' collections, January 16 - April 7, 2002 - Ghent, Gregory; McCue, Scott (Museum of Craft & Folk Art, 2002)
The Museum of Craft & Folk Art is pleased to present the exhibition Emblems of Passage: Art of Africa, Oceania, and the Americas, and to publish this catalog, co-produced with the Friends of Ethnic Art, as documentation of the exhibition. The exhibition has been organised from the collections of members of the Friends of Ethnic Art, a San Francisco Bay Area organization which for twenty-five years has promoted understanding and appreciation of tribal art from around the world.